Validation of the 10-Item Connor–Davidson Resilience Scale: The Case of Russian Youth - Nartova-Bochaver, Sofya; Korneev, Aleksei; Bochaver, Konstantin (Frontiers in Psychiatry, 2021)
This study validates the 10-item Connor-Davidson Resilience Scale (CD-RISC-10) on the Russian youth sample. A total of 689 respondents participated (Mage = 20.22, SDage = 2.08; 526 females). The Warwick-Edinburgh Mental Well-being Scale, the Positive and Negative Affects Schedule, the Centre of Epidemiological Studies-Depression Scale, the Rosenberg Self-Esteem Scale, and the Authenticity Scale were used to examine the content validity of CD-RISC-10. Two hypotheses were examined: that the Russian version of the CD-RISC-10 1) has structural validity (is unifactorial, as the original version) and 2) has convergent validity (which is proven by positive connections with psychological wellbeing and negative connections with ill-being). According to CFA, it was shown that the scale really had a unifactorial structure; its reliability was satisfactory (α = .85, ωh = .84). No age trends in the CD-RISC-10 scores were detected; in males, the scores were higher than in females. As expected, CD-RISC-10 was positively connected with mental wellbeing, positive affect, self-esteem, and authentic living while negatively with depressive symptoms, negative affect, accepting external influence, and self-alienation. The Russian version of CD-RISC-10 seems to be a valid, stable, and reliable instrument which may be recommended for use in various areas of research and practice.